Accounting and Taxation Knowledge as Predictors of Students Career Choices - Novia Hindayani; Dini Purnamasari (Universitas Sumatera Barat, 2026)
This study aims to analyze the effect of accounting knowledge and taxation knowledge on students’ interest in career choices. This research employs a quantitative approach using Structural Equation Modeling (SEM) based on Partial Least Square (PLS). The data used are primary data obtained through questionnaires distributed to 107 accounting students. The results show that accounting knowledge does not have a significant effect on students’ interest in career choices, as indicated by a t-statistic value of 0.615 and a p-value of 0.539. In contrast, taxation knowledge has a positive and significant effect on students’ interest in career choices, as indicated by a t-statistic value of 7.437 and a p-value of 0.000. Furthermore, the R-square value of 0.380 indicates that accounting knowledge and taxation knowledge are able to explain 38% of the variance in students’ career interest, while the remaining 62% is influenced by other variables outside the research model. The findings also reveal that taxation knowledge is the most dominant factor influencing students’ career interest. This study concludes that practical and applicable knowledge, particularly in taxation, plays a more significant role in shaping students’ career interests compared to theoretical knowledge.